2010
DOI: 10.1007/s10903-010-9406-9
|View full text |Cite
|
Sign up to set email alerts
|

Variations in Healthcare Access and Utilization Among Mexican Immigrants: The Role of Documentation Status

Abstract: The objective of this study is to identify differences in healthcare access and utilization among Mexican immigrants by documentation status. Cross-sectional survey data are analyzed to identify differences in healthcare access and utilization across Mexican immigrant categories. Multivariable logistic regression and the Blinder-Oaxaca decomposition are used to parse out differences into observed and unobserved components. Mexican immigrants ages 18 and above who are immigrants of California households and res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
194
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 254 publications
(208 citation statements)
references
References 40 publications
7
194
3
1
Order By: Relevance
“…Access to healthcare was examined in eight RFS and RFSH products, often by measuring by access to health insurance -one of the most common ways to measure healthcare access (MacKinney, Coburn, Lundlad, McBride, Mueller, & Watson, 2014). Due to interrelations between U.S. health policies, health systems, and immigration policies, employment and citizenship (Bustamante et al, 2012) insurance. This is an example of how outer systems (i.e., macrosystem, exosystem) interact and influence inner layer systems (e.g., individual and family health outcomes).…”
Section: Latina/o Families In Rural America: the Outer Systemsmentioning
confidence: 99%
“…Access to healthcare was examined in eight RFS and RFSH products, often by measuring by access to health insurance -one of the most common ways to measure healthcare access (MacKinney, Coburn, Lundlad, McBride, Mueller, & Watson, 2014). Due to interrelations between U.S. health policies, health systems, and immigration policies, employment and citizenship (Bustamante et al, 2012) insurance. This is an example of how outer systems (i.e., macrosystem, exosystem) interact and influence inner layer systems (e.g., individual and family health outcomes).…”
Section: Latina/o Families In Rural America: the Outer Systemsmentioning
confidence: 99%
“…Multilevel statistical models allow investigators to examine the influence of a factor at one level (e.g., an individual behavior such Vargas Bustamante et al 8 Thompson et al 9 Introductory and advanced public health coursework on principles of social epidemiology…”
Section: Multilevel Modelingmentioning
confidence: 99%
“…One of the main factors that delays seeking care among the undocumented is fear that their legal status will be uncovered if they access the health system [12,13]. A recent study that compared health care access and utilization among Mexican immigrants found that the undocumented were 27 percent less likely than documented immigrants to have a doctor visit in the previous year and 35 percent less likely to have a usual source of care [5].…”
Section: Health Care Utilization Among Immigrantsmentioning
confidence: 99%